PEMAHAMAN PUSTAKAWAN TERHADAP BIBLIOGRAFI NASIONAL INDONESIA - Rahmi Rahmi; Prita Wulandari; Nurwati Nurwati; Deine Pangalila; Shinta Tri Justicia (Perpustakaan Nasional RI, 2020)
The National Library of the Republic of Indonesia (National Library of Indonesia) publishes the Indonesian National Bibliography (BNI), which functions as a national bibliographic control. The bibliographic control is carried out by librarians at the provincial, district, and city levels. Therefore, understanding librarians are needed as an evaluation of BNI. Data collection through a literature review and a survey with two types of questions that consist of 30 multiple choices used to see the understanding of librarians, and 9 (nine) declarative survey questions by answering ‘yes’ and ‘no’ used to determine the situation of the library where respondents work with the use of BNI. From 64 respondents, the results of this study indicate that librarians’ understanding of BNI is fairly low with questions that can be answered by respondents ranging from 20%-78%, also 14 of 64 respondents get a range of values of 66% -80%. The findings also did not indicate the relationship between the librarians’ understanding of BNI and respondent demographics such as level of education, length of working in the library, and long working in the current unit.